2010
DOI: 10.1007/s10529-010-0230-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel method to obtain highly enriched cultures of adult rat Schwann cells

Abstract: Schwann cells (SCs) can be used to repair both the peripheral and central nervous systems. Therefore, establishment of a procedure to obtain activated, highly proliferative SCs, in an appropriate time for clinical applications, is a prerequisite. Purification is complicated by contamination with fibroblasts which often become the predominant cell type in an in vitro SC culture. This study describes a novel and efficient method to enrich SCs by utilizing the differential detachment properties of the two cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…However, it is important to note that this is not a comparative study. Peripheral nerve predegeneration takes advantage of Wallerian degeneration to obtain more and activated SCs in culture comparing to intact nerve culture (Niapour et al 2010). The duration of 10 days has been implemented for predegeneration period in this research, based on other studies in which the 7-10 days in vitro predegeneration resulted in the highest SCs purity in primary cultures (Kraus et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is important to note that this is not a comparative study. Peripheral nerve predegeneration takes advantage of Wallerian degeneration to obtain more and activated SCs in culture comparing to intact nerve culture (Niapour et al 2010). The duration of 10 days has been implemented for predegeneration period in this research, based on other studies in which the 7-10 days in vitro predegeneration resulted in the highest SCs purity in primary cultures (Kraus et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated well adjustments of both SCs and FBs with this modification. Primary plated cells were cultured with 2.5 % KOSR since our previous work and other studies have demonstrated optimal concentration of serum allowing SCs proliferation and hindering of FBs expansion (Niapour et al 2010;Takagi et al 2011). Given the identity of SCs, the neural crest stem cells medium was considered and adapted to SCs culture through addition of chemically defined ingredients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although successful, such strategies are technically complicated, costly, and may be limited by the high number of cells required for each intervention, which carries the risk of potential injury to the donor nerve, donor-site morbidity, and fibroblast contamination of cultures (Niapour et al 2010). Therefore, alternative sources of cells have been sought.…”
Section: Nerve Guidance Conduits Supplemented With Autologous Schwannmentioning
confidence: 99%